Development of Diabetes Care System to Reduce Hemoglobin A1C Levels in Diabetes Clinic, Dansai Crown Prince Hospital, Loei Province - Charoensup, Mettachit (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
This study aimed to develop and evaluate a diabetes care system to reduce hemoglobin A1C (HbA1C) levels at the diabetes clinic of Dansai Crown Prince Hospital, Loei Province. An action research methodology was employed over 6 months from April to September 2024, utilizing the Expanded Chronic Care Model (ECCM) with three components: self-care support, delivery system design, and clinical information systems. The study sample comprised 11 multidisciplinary healthcare team members and 208 diabetic patients with HbA1C levels ≥ 8%, selected through purposive sampling. Research instruments included questionnaires on diabetes knowledge and behavioral modification, and satisfaction assessment questionnaire. Content validity indices were 0.92 and 0.93, with reliability coefficients of 0.95 and 0.91, respectively. Data were analyzed using means and standard deviations. Results showed that following implementation of the care system, patients achieved a mean knowledge score of 17.97 (SD=4.85), classified as high level, increased from 12.56 (SD=5.23). Mean behavioral score was 9.94 (SD=3.46), classified as high level, increased from 4.54 (SD=2.23). Mean HbA1C level was 6.87% (SD=0.57), significantly decreased from pre-implementation level of 8.76% (SD=0.76). Although still classified as uncontrolled, the 1.89% reduction was clinically significant. Overall satisfaction with the system was at the highest level (mean=4.63, SD=0.13). Recommendations include broader implementation of the system with adaptations to fit individual hospital contexts to enhance flexibility and effectiveness. Study limitations include absence of a control group, short follow-up period of 6 months, and purposive sampling method.